HazMat awareness training manual - Melander, Paul (Thomson/Delmar Learning, 2005)
This training manual is part of an innovative training program, developed in conjunction with the North American Transportation Management Institute (NATMI). It utilizes a seminar format that concentrates on all levels of hazardous materials training. Transportation of hazardous materials by the trucking industry is covered in depth, as well as issues of compliance of carrier companies and individual truck drivers with Department of Transportation (DOT) regulations. Coverage meets the needs of carriers to provide HazMat refresher training that is required at least once every three years. Issues of safety and security of trucking fleets, including HazMat handling, are also addressed to help ensure that the carrier's safety management team fulfills the task of making sure that truck drivers are trained on the transport of hazardous materials